Estudios sobre la transmisión del virus del rayado fino del maíz por el cicadelido Dalbulus maidis (De L. & W.) - González, V.R. (IICA, San José (Costa Rica), 2014)
Tesis (Mag. Sc.) -- CATIE, Turrialba (Costa Rica), 1969